Studies Of Some 3, 4-Dichlorophenacyl Esters Derivatives: Synthesis, Characterization, Crystal Structure Determination And Antioxidant Properties - Sim, Ai Jia (2021)
In this research, a series of nineteen 3, 4-dichlorophenacyl esters 2(a−s) were synthesized and crystallized by using slow evaporation method. The crystal structures were characterized by FT-IR and NMR spectroscopic analyses and further determined by single crystal X-ray crystallography technique (except 2o and 2s). The molecular conformation and crystal packing of these compounds were studied crystallographically. Eight compounds crystallized in monoclinic P21/c or P21/n space group, seven in triclinic